Entre a Amnésia e a Vontade de nada Esquecer: notas sobre regimes de historicidade e história oral - Garnica, Antonio Vicente Marafioti [UNESP]; Fernandes, Déa Nunes; Da Silva, Heloisa [UNESP] (My University, 2011)
In this paper we intend to sketch a configuration of the research practices of the Research Group Oral History and Mathematics Education (GHOEM) and, in general terms, to explain some concepts and procedures in which these practices are founded. In order to do this, the expression Regimes of Historicity - meaning the different ways of articulating the notions of present, past and future - is initially mobilized. By this expression we are able to understand the emergence of the discourse that underpins a set of actions and theoretical frameworks for the research in Mathematics Education and more particularly, for the Historiography of Mathematics Education.
Between amnesia and the desire not to forget: An essay on regimes of historicity and oral history
Keywords: GHOEM; Mathematics education; Oral history; Regimes of historicity